Names of Javanese Generation Z and Alpha in Patemon Village, Tengaran Subdistrict, Semarang Regency - Wahyuloh, Aditiyas Anggoro; Joko Sukoyo; Nur Fateah (Sutasoma : Jurnal Sastra Jawa, 2025)
A name is an element of identity that is not only personal but also reflects the social, cultural, and historical background of its owner. The Javanese people's practice of giving names to their children undergoes significant changes from one generation to the next. This study aims to determine the pattern of Javanese names, particularly among Generation Z and Alpha in Patemon Village, Tengaran Subdistrict, Semarang Regency. This research method employs a descriptive qualitative approach, utilizing data collection techniques that include interviews, observation, and literature review. Data analysis for this research was conducted through the stages of data reduction, data presentation, and conclusion. The results of this study show that the variation in the names of Generation Z and Alpha in Patemon Village, Tengaran Subdistrict, Semarang Regency, still retains full Javanese language elements, amounting to as much as 8% and combining Javanese elements with foreign languages as much as 47%, with the combination of Javanese and Arabic elements dominating as much as 65%, English elements 15%, Latin elements 10%, Spanish / Portuguese 5% and other language elements 5%. Then, those who use foreign language elements in full are 45%, with Arabic elements accounting for 70%, English elements for 20%, Latin elements for 5%, German elements for 3%, and other language elements for 2%.  The implication of this study is the need for an in-depth examination of the sustainability of Javanese cultural heritage in terms of personal naming practices.